Influence of tunneling barrier width on the forward current characteristics of InAs-based microwave p–n diode. Issue 12 (December 2015) - Yang, Chih Chin; Su, Yan Kuin; Lin, Hao Hsiung
Abstract: InAs-based p–n interband tunneling bi-barrier resonant microwave (ITE BBRM) devices were successfully fabricated by using the molecular beam epitaxial (MBE) method in this research. The influence of a central barrier thickness from 10 Å to 40 Å on electrical characteristics of BBRM devices was investigated by using theoretical analysis and experimental evidence. Tunneling current densities ( JT ) of BBRM devices were simulated in accordance with the consideration of a narrowing bandgap (NBG) effect caused by the heavy concentration doped (HCD) effect. The peak-to-valley current ratio (PVCR) value and output current density reached as high as 383 and 0.226 kA/cm 2 in practice, respectively, when the central barrier thickness was 10 Å thick. When an InAs-based p–n BBRM device produces a resonant phenomenon, the resonant operation voltage of the device is as low as 2.03 V in our experimental study. Experimental results of the tunneling current density are matched to the calculating results of device from the calculation of quantum energy levels. The thinner the tunneling barrier thickness between the double quantum wells, the more the tunneling current density, which is attributed to the larger transmittance coefficient. In this study, an increase in the central barrier thickness increased the resistive cutoff frequency ( fr ), which the frequency reached GHz indicating that the ITE BBRM device became a microwave resonant device. Graphical abstract: Highlights: Influence of barrier thickness in electrical properties of ITE BBRM is explored. PVCR and output current density reach as high as 383 and 0.226 kA/cm 2 respectively. Resonant operation voltage of ITE BBRM is as low as 2.03 V. Increase of central barrier thickness raises up the resistive cutoff frequency ( fr ). The frequency ( fr ) reaches as GHz indicating that ITE BBRM becomes microwave device. Frequency ( fr ) of ITE BBRM could be enhanced through changing barrier thickness.